Adaptation process of a Korean traditional house to modern dwelling culture: focusing on Hui-Dong Go’s house (1918-1959) in Wonseo-dong, Seoul - Keehwang Jung; Hoyoung Kim (Journal of Asian Architecture and Building Engineering)
Housing in the Joseon Dynasty was regulated by the caste system based on Confucianism and the perceived predominance of men over women. Therefore, the houses and associated dwelling culture of the Joseon populace did not evolve and became stagnant. Although new dwelling cultures and associated houses from abroad through the Gaehwa and the 1876 port-opening were introduced, the dwelling cultures led to stagnant evolution of the houses of the Joseon populace. In this sense, Hui-Dong Go’s house is an extremely rare case, having been built in a relatively economically manner on the parcel of a typical house. Therefore, the current work analyzes Go’s house in comparison with houses proposed in the discourses of pre-modern and modern dwelling culture at the time in Joseon both before and after the 1876 port-opening, and it then examines the meanings of the dwelling culture that can be drawn from his house. As a result, this study reveals that Go’s house is a highly valuable integration of the dwelling culture, which succeeded the traditional type of Korean housing, improved upon both the problems of Joseon houses and the problems of urban hanoks, and actively accepted and adapted modern residential discourses.